Contribution Locus of Control and Self Esteem to Student Academic Procrastination (Study at Department of Islamic Guidance And Counseling, IAIN IB Padang) - Batubara, Juliana; Asriatuzzeky, Asriatuzzeky (Universitas Muhammadiyah Metro, 2017)
This study aims to: (1) describe the locus of control, self-esteem and student academic procrastination (2) express the contribution of locus of control and self-esteem to student academic procrastination. This research is conducted by the expost-facto method with questionnaire instrument which has been measured its validity and reliability. The population in this study were BKI FTK IAIN IB Padang students entering 2014, 2013 and 2012 totaling 355 people, the samples used were Stratified Proportional Random Sampling technique so that the sample of 107 students was obtained. Sample amounted to 107 students. The result of the research shows that (1) locus of control is classified moderately, student self-esteem is on average high and student academic procrastination rate is high. (2) there is a significant contribution between locus of control and self-esteem on student academic procrastination jointly equal to 18.8%.